Amphotericin B Loaded Polymeric Nanoparticles for Treatment of Leishmania Infections - Mudassara Saqib; A. Shabbir Ali Bhatti; Nasir M. Ahmad; Naveed Ahmed; Gul Shahnaz; Noureddine Lebaz; Abdelhamid Elaissari (Nanomaterials, 2020)
Fungal infections in immune-compromised patients are an important cause of mortality and morbidity. Amphotericin B (Amp B) is considered a powerful fungicidal drug but its clinical usage has certain limitations when administered intravenously due to its toxicity and poor solubility. In consideration of such challenges, in cutaneous leishmaniasis, the topical application of Amp B can be a safer option in many aspects. Thus, herein, biopolymer of polycaprolactone (PCL) nanoparticles (NPs) were developed with the loading of Amp B by nanoprecipitation for the treatment of topical leishmanial infections. Various parameters, such as concentration of PCL and surfactant Poloxamer 407, were varied in order to optimize the formation of nanoparticles for the loading of Amp B. The optimized formulation exhibited a mean hydrodynamic particle size of 183 nm with a spherical morphology and an encapsulation efficiency of 85%. The applications of various kinetic models reveal that drug release from nanoformulation follows Korsmeyer–Peppas kinetics and has a high diffusion exponent at a physiological pH of 7.4 as well a skin relevant pH = 5.5. The activity of the prepared nanoparticles was also demonstrated in Leishmania infected macrophages. The measured IC50 of the prepared nanoparticle formulation was observed to be significantly lower when compared to control free Amp B and AmBisome® for both L. tropica KWH23 and L. donovani amastigotes in order to demonstrate maximum parasite inhibition. The prepared topical nanoformulations are capable of providing novel options for the treatment of leishmaniasis, which can be possible after in vivo assays as well as the establishment of safety profiles.